Can organized leisure-time activities buffer the negative outcomes of unstructured activities for adolescents' health? - Badura, Petr; Madarasova Geckova, Andrea; Sigmundova, Dagmar; Sigmund, Erik; van Dijk, Jitse P; Reijneveld, Sijmen A (International journal of public health, 2018)
OBJECTIVES: We aimed to assess the associations of involvement in selected unstructured activities (UA) with health-risk behaviours and academic achievement and the degree to which the participation in organized leisure-time activities (OLTA) changes these associations. METHODS: Using a sample of 6935 Czech adolescents aged 13 and 15 years, we investigated adolescents' weekly involvement in hanging out, visiting shopping malls for fun and meeting friends after 8 p.m., OLTA and engagement in three health-risk behaviours and academic achievement. RESULTS: Weekly involvement in the selected UA was associated with higher odds for regular smoking, being drunk, having early sexual intercourse and low academic achievement. Concurrent participation in OLTA did not buffer these negative outcomes, except for sexual experience. However, those highly engaged only in UA were more likely to participate in the health-risk behaviours and report worse academic achievement than those participating in any OLTA concurrently. CONCLUSIONS: The selected UA are strongly associated with an increased occurrence of adolescents' health-risk behaviours and low academic achievement. Concurrent participation in OLTA does not buffer these negative outcomes significantly, but adolescents engaged only in UA consistently report the least favourable outcomes.
Keywords: školní úspěšnost; Leisure Activities; Male; Adolescent; Česká republika; Extracurricular activities; zdravotně rizikové chování; Substance use; otrava alkoholem; School performance; mužské pohlaví; Sexual intercourse; Smoking; mladiství; Czech Republic; Health Risk Behaviors; lidé; ženské pohlaví; Adolescence; volnočasové aktivity; Humans; Academic Success; sexuální chování; Sexual Behavior; Unstructured leisure; Alcoholic Intoxication; Female; kouření